DIFFERENCES IN THE LEVEL OF ANXIETY OF PREGNANT WOMEN IN THE I, II, AND III TRIMESTER - Rachma, Gading Nurhafiza; Irwanto, Irwanto; Izzati, Dwi (UNIVERSITAS AIRLANGGA, 2024)
Background: Pregnancy is a physiological period that requires various adjustments to the changes that occur and can induce anxiety. Anxiety during pregnancy can be experienced from the first trimester to the third trimester. This anxiety can have negative impacts on both the mother and the fetus. This research aimed to determine the differences in the anxiety levels of pregnant women in the first, second, and third trimesters in the working area of the Gading Surabaya Health Center. Method: This is a quantitative research with an observational analytic method and a cross-sectional design. The study population consists of pregnant women in the first, second, and third trimesters in the working area of Gading Surabaya Health Center. The study involved 100 samples of pregnant women in the first, second, and third trimesters selected using the simple random sampling method. The instrument used is a questionnaire, namely the Perinatal Anxiety Screening Scale (PASS). The analysis method used is the Kruskal-Wallis test. Results: The statistical test results show a p-value (0.023) < α (0.05), indicating a significant difference in anxiety levels among pregnant women in the first, second, and third trimesters. Most pregnant women in the first trimester (56.7%) and second trimester (70.7%) did not experience anxiety symptoms, while pregnant women in the third trimester (51.7%) experienced mild to moderate anxiety. Conclusion: There is a significant difference in anxiety levels among pregnant women in the first, second, and third trimesters.